Divine Love in the Thought of Rabi’ah Adawiyya and Its Comparison with the Poetry of Hafez Shirazi - Mirghaderi, Seyyed Fazlollah; Hosseini Mirabadi, Habibollah; Dehghani, Leila (LANGUAGE ART, 2024)
At a time when asceticism was the dominant approach among mystics, Rabi’ah Adawiyya introduced the concept of divine love and mystical devotion. In the centuries following Rabia, divine love remained one of the most fundamental themes in the works of Persian mystical poets. This research explores the prominent aspects of Rabia’s mystical love through an investigative lens and then compares them with the poetry of Khwaja Hafez Shirazi, identifying their similarities. The study adopts a qualitative approach, relying on descriptive-analytical and comparative methods. The comparative framework is based on the American school of comparative literature, which emphasizes parallels and affinities. The findings reveal that the key characteristics of Rabia’s mysticism include: “Pure love”, “Beholding the Beloved’s beauty”, “Not diverting from the Creator to the creation”, “Preferring the Friend over the world and its people”, “Night vigils and devotion”, “Weeping in separation from the Beloved”, “The lover’s immersion in the Beloved”, “The station of intimate friendship” (Khalwat), these elements can also be observed in Hafez’s poetry. Although Hafez expresses these concepts in a more eloquent and captivating manner, their origins can be traced back to Rabia’s thought.